LEGAL AND SOCIAL STATUS OF MODERN WOMEN - Sergeyevna Lavrentieva, Maria; Mikhailovich Turkin, Mikhail; Olegovna Tchinaryan, Elena (Revista Inclusiones, 2020)
The article attempts to conduct an in-depth analysis of the problems related to the place and role of women both in Russian society and the world. In this regard, the socio-legal approach to understanding the purpose of a woman, her status, and role in modern society has been analyzed. The authors have analyzed various international aspects related to the social and legal status of women in the modern world, the changing status and role of women in modern conditions, as well as a new system of values designed to relieve tension in society through the practice of social creativity implemented in women’s social initiatives.